Chebycheff approximation in system identification and model reduction - Coutlis, A; Limebeer, D (1997)
The aim of this paper is to show how Chebycheff approximation may be used in frequency weighted ℋ∞ system identification and model reduction. We show how these techniques may be combined with known results from Hankel norm model reduction theory to reduce the error between the plant and the low-order approximation. In identification we also apply an ℒ∞-norm variant of Levy's method (Levy, 1959). © 1997 Elsevier Science Ltd.